Additive Manufacturing for Aerospace from Inception to Certification. (21st May 2022) - Balaji, Devarajan; Ranga, Jarabala; Bhuvaneswari, V.; Arulmurugan, B.; Rajeshkumar, L.; Manimohan, Mohan Prasad; Devi, G. Ramya; Ramya, G.; Masi, Chandran
Abstract : Metal additive manufacturing (MAM) does not require any preface for its potential applications in various engineering and technological sectors. This article comprehensively discusses about the application of additive manufacturing technique specifically aerospace components. The structure of this article begins with an introduction to the current state-of-the-art MAM technologies with the aid of patent landscape analysis. Any manufacturing starts with understating of the manufacturing cycle, so herein, the aerospace manufacturing cycle has been discussed commencing from the design phase and followed by the process parameters selection. The immediate effect after printing is the selection of evaluation parameters, wherein the surface texture analysis of AM printed components is discussed. This paves to discuss about the specific alloys such as titanium alloy and Inconel alloys which are widely used in the aerospace industry. This analysis paves a path for the utilization of these materials to manufacture specific aerospace components which are also discussed. Thereby, the impact of MAM over the aerospace sector and the guidelines to decision making on the suitable variant of MAM has been discussed clearly with the help of earlier literatures. Finally, the qualification and certification procedure are discussed therein, leading to the conclusion about the future scope of MAM in the aerospace sector.